2012
DOI: 10.1136/bmj.e1203
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease in kidney donors: matched cohort study

Abstract: Objective To determine whether people who donate a kidney have an increased risk of cardiovascular disease.Design Retrospective population based matched cohort study.Participants All people who were carefully selected to become a living kidney donor in the province of Ontario, Canada, between 1992 and 2009. The information in donor charts was manually reviewed and linked to provincial healthcare databases. Matched non-donors were selected from the healthiest segment of the general population. A total of 2028 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
140
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(142 citation statements)
references
References 30 publications
2
140
0
Order By: Relevance
“…The largest of these studies in the United States was limited by the inclusion of primarily white donors who donated in an era when conditions such as hypertension and obesity were less common and usually were exclusions for donation (2). Subsequent work confirmed a lower risk of death and cardiovascular disease in donors compared with healthy persons in the general population who may have been suitable to donate (6)(7)(8). Two recent studies, however, reported an increased risk of ESRD in donors compared with control groups derived from healthy participants in unrelated epidemiological studies (9,10).…”
Section: Uncertainty About the Long-term Risk Of Donationmentioning
confidence: 99%
“…The largest of these studies in the United States was limited by the inclusion of primarily white donors who donated in an era when conditions such as hypertension and obesity were less common and usually were exclusions for donation (2). Subsequent work confirmed a lower risk of death and cardiovascular disease in donors compared with healthy persons in the general population who may have been suitable to donate (6)(7)(8). Two recent studies, however, reported an increased risk of ESRD in donors compared with control groups derived from healthy participants in unrelated epidemiological studies (9,10).…”
Section: Uncertainty About the Long-term Risk Of Donationmentioning
confidence: 99%
“…Understanding of the medical risks to living kidney donors is evolving, with the progressive publication of more robust long-term data (7)(8)(9). Recent evidence of small absolute increases in the risk of ESKD, hypertension, hypertension in pregnancy, and allcause mortality in donors in the three decades after donation, compared with the general or healthy population (4,7,8,(10)(11)(12)(13), reinforces the need for ongoing research and follow-up of living kidney donors.…”
Section: Introductionmentioning
confidence: 99%
“…These databases have been used extensively to research health outcomes. [18][19][20][21][22] Whenever possible, we defined patient characteristics, surgery characteristics and outcomes using database codes that have been proven reliable when compared with manual chart review (Ap pendices 1 and 2, available at www .cmaj .ca /lookup /suppl /doi :10.1503/cmaj.110895/-/DC1).…”
Section: Data Sourcesmentioning
confidence: 99%